Marketing strategy for museums : a practical guide - Lister, Christina (Routledge, 2023)
"Marketing Strategy for Museums is a practical guide to developing and delivering marketing that supports museums' missions and goals. Explaining how museums can be strategic and proactive in their approach, it also shows how to make effective decisions with limited resources. Presenting examples from a range of museums around the world, the author positions marketing as a vital function that aims to build mutually beneficial relationships between museums and their audiences--both existing and new--and ensure museums are relevant and viable. Breaking down key marketing models, Lister shows how they can be applied to museums in a meaningful way. Setting out a step-by-step framework for developing a museum's marketing strategy and for creating marketing campaigns, which can be scaled up or down. Readers will also be encouraged to reflect on topics such as sustainable marketing; ethical marketing; and accessible and inclusive marketing. Marketing Strategy for Museums provides an accessible guide that seeks to demystify marketing and boost the confidence of those responsible for planning and delivering marketing in museums. It is aimed at people working in museums of all types and sizes and will also be relevant to students of museum and heritage studies"-- Provided by publisher.
Keywords: Museums -- Marketing.; elektronické knihy; electronic books